2017
DOI: 10.1007/s40122-017-0066-5
|View full text |Cite
|
Sign up to set email alerts
|

Parecoxib Provides Analgesic and Opioid-Sparing Effects Following Major Orthopedic Surgery: A Subset Analysis of a Randomized, Placebo-Controlled Clinical Trial

Abstract: IntroductionOrthopedic surgeries are among the most common and most painful surgeries performed. A multimodal analgesic approach is recommended to reduce opioid consumption, provide effective pain relief, and improve outcomes following surgery. This study examined the efficacy and opioid-sparing effects of parecoxib following major orthopedic surgery.MethodsThis subset analysis of a large, multicenter, randomized, double-blind, placebo-controlled study of parecoxib examined treatment effects on postoperative p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…A recent comprehensive review of all parecoxib trials reported consistent outcomes across all trials, regardless of the populations or comparators included 26. Analyses of subpopulations of the main trial also showed very similar outcomes regardless of surgery type 2325. The trial that the present analysis was based on included 113 centers from 14 different countries.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…A recent comprehensive review of all parecoxib trials reported consistent outcomes across all trials, regardless of the populations or comparators included 26. Analyses of subpopulations of the main trial also showed very similar outcomes regardless of surgery type 2325. The trial that the present analysis was based on included 113 centers from 14 different countries.…”
Section: Discussionmentioning
confidence: 59%
“…Recently, subpopulation analyses have confirmed that these results are consistently observed across subpopulations defined according to surgery types too 2325…”
Section: Resultsmentioning
confidence: 70%
“…As narcotic use was not associated with KOOS subscale scores or HSS Pedi-FABS scores, patients should be switched to an analgesic with less addictive potential as soon as their pain levels permit. Previous studies have identified ways to decrease opioid use after orthopaedic surgery, such as through acetominophen 52 , 60 or parecoxib 11 , 23 , 34 administration. With opioid-related deaths increasing 17 and documented negative effects of opioids after surgery, 20 providers should attempt to use a multimodal pain-management strategy to reduce opioid addiction burden on patients.…”
Section: Discussionmentioning
confidence: 99%
“…A pooled analysis of 28 randomized, placebo-controlled clinical trials with 9287 patients has shown that skin rash and cardiac complications occur infrequently with parecoxib administration, which highlight its safety in patients (Schug et al, 2017). Currently, it is approved in over 80 countries for perioperative pain control and may help reduce opioid use (Diaz-Borjon et al, 2017).…”
Section: Amide Prodrugsmentioning
confidence: 99%